2020
DOI: 10.3390/vaccines8040706
|View full text |Cite
|
Sign up to set email alerts
|

DC-Based Vaccines for Cancer Immunotherapy

Abstract: As the sentinels of the immune system, dendritic cells (DCs) play a critical role in initiating and regulating antigen-specific immune responses. Cross-priming, a process that DCs activate CD8 T cells by cross-presenting exogenous antigens onto their MHCI (Major Histocompatibility Complex class I), plays a critical role in mediating CD8 T cell immunity as well as tolerance. Current DC vaccines have remained largely unsuccessful despite their ability to potentiate both effector and memory CD8 T cell responses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 130 publications
0
69
0
Order By: Relevance
“…DEXs also possess more peptide-MHC I and -MHC II complexes than DCs, thereby rendering the use of DEXs a less time-and space-consuming strategy (Figure 2A) (66)(67)(68). Additionally, DEXs are more resistant to immunosuppressive mechanisms in the tumor microenvironment than DCs (69). Exosomes are reportedly more capable of inducing immunocompetence in DCs than in microvesicles.…”
Section: Exosome-based Vaccines As a Cancer Therapeutic Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…DEXs also possess more peptide-MHC I and -MHC II complexes than DCs, thereby rendering the use of DEXs a less time-and space-consuming strategy (Figure 2A) (66)(67)(68). Additionally, DEXs are more resistant to immunosuppressive mechanisms in the tumor microenvironment than DCs (69). Exosomes are reportedly more capable of inducing immunocompetence in DCs than in microvesicles.…”
Section: Exosome-based Vaccines As a Cancer Therapeutic Strategymentioning
confidence: 99%
“…According to Fu and colleagues, the lack of an immune response to these vaccines can be associated with the DC type selected by researchers in these clinical trials (69). They used immature DCs, while other studies showed that exosomes derived from mature DCs induced more potent T-cell priming.…”
Section: Clinical Trials Using Exosome-based Vaccinesmentioning
confidence: 99%
“…This nanobody technology has proven successful at targeting lentiviral vectors to murine DCs both in vitro and in situ and has previously been discussed [75,76]. Further, because of their ability to mediate host effector and memory CD8+ T cell responses, which is crucial for anti-tumor immunity, DC-based vaccines have become one of the leading strategies for cancer immunotherapy [77]. However, in the case of therapeutic HIV vaccines, vector-transduced DCs can themselves act as latency-reversing agents (LRAs) by secreting high levels of cytokines, such as TNF-α, and they are also capable of homing to lymphoid tissues where latently-infected viral reservoirs reside to potentially activate latent viral reservoirs.…”
Section: Lentiviral Vector Approach For Hiv Dna Vaccines and Dendritic Cell Targetingmentioning
confidence: 99%
“…The advantages of DC vaccines include their personalized nature, the feasibility of producing an immune response since dendritic cells are major players in the activation of adaptive responses, their ability to specify the response towards one antigen or a group of antigens and the relatively safety in individuals as they do not cause AEs (108). By contrast, DC-based vaccines, similar to other vaccines, face certain hurdles, such as tumor immunosuppression and the limited functions of monocyte-derived dendritic cells, which are the cells used to generate this type of vaccines (109). In addition, since they are personalized, DC vaccines tend to be expensive (109).…”
Section: Cancer Vaccines: Types and Therapeutic Combinationsmentioning
confidence: 99%
“…By contrast, DC-based vaccines, similar to other vaccines, face certain hurdles, such as tumor immunosuppression and the limited functions of monocyte-derived dendritic cells, which are the cells used to generate this type of vaccines (109). In addition, since they are personalized, DC vaccines tend to be expensive (109). As with other types of vaccines, DC vaccines suppress tumor growth and increase the number of T cells infiltrating the tumor microenvironment, which can be more efficient compared with other types of vaccines in certain cases, such as in murine lung carcinoma (LL2), the study was done in vitro and the DC vaccine was able to exhibit superior immunogenicity compared with an antigen-adjuvant vaccine (102).…”
Section: Cancer Vaccines: Types and Therapeutic Combinationsmentioning
confidence: 99%